Pengaruh Penggunaan Polyethylene Terephthalate sebagai Agregat Halus terhadap Kuat Lentur Beton - Kusuma, Santos Surya; Indriani, Andi Marini; Utomo, Gunaedy (Universitas Ibn Khaldun, 2024)
The use of plastic in the city of Balikpapan in currently often used in daily activities, causing plastic waste in the city of Balikpapan to contribute up to 17% of the total waste production. The use of plastic in the world of construction has begun by using PET (Polyethylene Terephthalate) plastic as a concrete mixture. With its utilization, it can be a solution to reduce the production of plastic waste in the city of Balikpapan. In this research, PET plastic was used as a concrete mixture with a percentage of 0.7% and combined with local materials from East Kalimantan as a form of supporting the relocation of the state capital to East Kalimantan province. The purpose of this study was to determine the effect of using PET type plastic as fine aggregate on the flexural strength of concrete. The method used in this study is the experimental method with a test sample measuring 15x15x60 cm. The test results showed that normal concrete got a slump value of 10 cm and the PET variation was 7% 9 cm with the flexural strength test results of normal concrete with a curing period of 14 and 28 days getting a value of 3,044 MPa and 3,188 MPa, PET variations of 0.7% 14 and 28 days got a value of 2,370 MPa and 2,423 MPa, based on the results of this study it can be concluded that the use of PET plastic as fine aggregate experienced a decrease in the quality and weight of the sample due to the smooth and slippery texture of PET plastic causing the concrete mixing process to be poor.